2016
DOI: 10.1038/srep35756
|View full text |Cite
|
Sign up to set email alerts
|

Euchromatin histone methyltransferase 1 regulates cortical neuronal network development

Abstract: Heterozygous mutations or deletions in the human Euchromatin histone methyltransferase 1 (EHMT1) gene cause Kleefstra syndrome, a neurodevelopmental disorder that is characterized by autistic-like features and severe intellectual disability (ID). Neurodevelopmental disorders including ID and autism may be related to deficits in activity-dependent wiring of brain circuits during development. Although Kleefstra syndrome has been associated with dendritic and synaptic defects in mice and Drosophila, little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 64 publications
(90 reference statements)
2
31
0
1
Order By: Relevance
“…We found that for control iNeuron networks the pattern of activity changed progressively over a period of several weeks ( Fig. 2B-F), similar to what we have observed previously in rodent neuronal cultures 29 . In particular, during the first three weeks of differentiation, (CV) of the inter-burst interval (P<0.0001) ( Fig.…”
Section: Neuronal Network Of Ks Ineurons Show An Aberrant Pattern Ofsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that for control iNeuron networks the pattern of activity changed progressively over a period of several weeks ( Fig. 2B-F), similar to what we have observed previously in rodent neuronal cultures 29 . In particular, during the first three weeks of differentiation, (CV) of the inter-burst interval (P<0.0001) ( Fig.…”
Section: Neuronal Network Of Ks Ineurons Show An Aberrant Pattern Ofsupporting
confidence: 88%
“…Indeed, we found that network bursts also occurred with a lower frequency, longer duration and irregular pattern in dissociated neuronal networks from either embryonic rats (i.e. where Ehmt1 was downregulated through RNA interference 29 ). This indicates that some network parameters are consistently and similarly altered in divergent KS models.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, EHMT1 can be viewed as a dynamic regulatory histone mark instead of a generic heterochromatin mark [Benevento et al, 2016]. EMHT1 has been demonstrated to be essential for neural network activity, action potential coherency, and burst time during brain development [Bart Martens et al, 2016]: EHMT1 loss may therefore potentially lead to structural and functional anomalies in the developed brain.…”
mentioning
confidence: 99%
“…The mouse homolog has been shown to specifically regulate the expression of several activity-dependent genes in the hippocampus following fear conditioning 10 . Furthermore, it has been shown to be critically involved in homeostatic synaptic scaling in vitro and in the developing visual cortex in vivo 11,12 . Ehmt1 +/mice recapitulate core features of the human phenotype: they show delayed postnatal development and facial and cranial abnormalities that correspond to the phenotype observed in human patients 13 .…”
Section: Introductionmentioning
confidence: 99%